La prévision de faillite dans l’industrie de l’assurance-vie : cas : les Coopérants - Derez, Patricia (Assurances, 1994)
Financial markets are becoming increasingly concerned with evaluating the financial health of life insurance companies. Life insurers are no longer as solvent as they were in the past. This article aims to establish whether the American model developed by Ran Barniv and Robert A. Hershbarger would have been adequate to predict the bankruptcy of Les Coopérants, one of the first life insurance company to fail in Canada. The Barniv and Hershbarger model uses three types of multivariate analyses and has obtained very good classification ratings when it was validated. Using univariate and multivariate analyses, this article illustrates the effectiveness of the model by applying it to Les Coopérants and comparing it to two solvent companies: Assurance-vie Desjardins and Industrial-Alliance. The author also points out the important and significant variables in identifying the financial difficulties of a life insurer.